Trading Identities: The Souvenir in Native North American Art from the Northeast, 1700-1900 - Phillips, Ruth B. (Ruth Bliss) (McGill-Queen's University Press, 1998)
Indians in northeastern North America produced a variety of art objects for sale to travelers and tourists during the 18th and 19th centuries. This art is of high quality and great aesthetic interest, but has been largely ignored by scholars. This study combines fieldwork, art historical analysis
Section: xvii, 334 pages : illustrations (certaines en couleur)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé